Retrospective comparison of surgical techniques used in the hypospadias treatment - Hikmet Zeytun (Dicle Medical Journal, 2013)
Objectives: The aim of this study was to investigate theresults of hypospadias surgery.Methods: In this study the results of 87 patients who underwenthypospadias repair surgery between 2005 and2010 were evaluated retrospectly.Results: 21 patients; Meatal Advancement and Glanuloplasty(MAGPI), 33 patients; Tubularized Incised PlateUrethroplasty (TIPU), 21 patients; Parameatal Based Flap(Mathieu), 6 patients; Mathieu and Incision Sutured (MAVIS)and the other 6 patients were operated via TransversTubularized Preputial Island Flap (TTPIF). To prevent fistulaformation double layer dartos flap (DLDF) was appliedto all patients to whom MAVIS had been applied andto 27 of the patients to whom TIPU had been applied, andtunica vaginalis flap over neourethra was placed to thepatients to whom TTPIF was applied. While fistula wasnot seen in the patients to whom flap was used, it wasseen that the urethrocutaneous fistula ratio was high inthe patients without flap uses.Conclusion: TIPU is a kind of method which can beeasily applied and preferred regardless of localizationof urethral meatus. A barrier layer placed between skinand neourethra to prevent fistula formation significantlydecreases the fistula ratio. Preputial dartos flap is a goodpreference, But tunica vaginalis must be kept in mind asan alternative to this flap in the patients who underwenturethroplasty with preputial dartos flap or who had circumflexbefore. TTPIF can be used as an alternative methodto TIPU method in patients with more proximal localizedhypospadias, especially if the urethral plate was exicedbecause of chordee and it is successful when combinedwith tunica vaginalis flap.Key words: Hypospadias, urocutaneous fistula, flap